Modelling for compressive buckling of reinforcing bars. Issue 9 (16th November 2018) - Qiu, Jianlei; Gong, Jinxin; Zhang, Qin; Feng, Zhibin
Abstract : Buckling of longitudinal bars is a common failure mode in reinforced concrete columns under earthquake, and can lead to the deterioration of structural seismic performance. In this study, a numerical method for predicting the average behaviour of reinforcing bars in compression considering the influences of buckling is developed. The bare reinforcing bar is divided into several segments, and a set of differential equations is established, in which both the material and geometrical non-linearities are taken into account. Then, a set of non-linear equations is derived by solving these differential equations and combining the conditions of geometrical compatibility and mechanical equilibrium so that the uniaxial compression stress–strain relations of buckling bars can be calculated numerically. The developed numerical method is verified against experimental data. The results of simulation and test are analysed; it is found that, unlike the case of elastic buckling, buckling of the reinforcing bars with commonly used bar length-to-diameter ratio usually occurs in the post-yield stage, and the degradation of post-buckling stress is mainly affected by the bar length-to-diameter ratio, the yield strength and the ultimate strength-to-yield strength ratio. Finally, a pseudo-material stress–strain relationship of a reinforcing bar in compression considering the effects of buckling is established by performing parametric analysis.